Ibrah Acquisition: A New Concept of Absorptive Capability Based on Islamic Value - Widianti, Hesti; Harjanti, Ririh Sri; Rahmadiane, Ghea Dwi (International Journal of Economics, Management and Accounting, 2025)
This study aims at introducing a new concept; the integration of absorptive capacity theory and ibrah value—this value derived from Islamic values, namely ibrah acquisition (IA). Absorptive emphasizes the company’s ability to recognize the importance of new information, assimilate it, and apply it for commercial purposes. Meanwhile, ibrah is an effort to take lessons from the experiences of other parties or events that occurred in the past through deep thinking. Thus, ibrah acquisition is defined as the company’s ability to absorb external knowledge from various events, history, and experiences based on values and measures that are more rationally applied in the company to realize optimal company performance. The concept of ibrah acquisition includes seven newly developed dimensions presented in this article’s contribution, framed in the main competency categories. They are prior investments, prior knowledge, motivation for collecting knowledge, and direction of knowledge with dimensions for scale development, namely aqidah, morals, and belief.